Semantic memory: Which side are you on?. (September 2015) - Patterson, Karalyn; Kopelman, Michael D.; Woollams, Anna M.; Brownsett, Sonia L.E.; Geranmayeh, Fatemeh; Wise, Richard J.S.
Abstract: We present two patients in whom the combination of lesion site and cognitive performance was uniquely informative about the organisation and functional anatomy of semantic memory. One had had a single lobar stroke with an unusual distribution, largely destroying the whole of the left temporal lobe ventral to the superior temporal sulcus. The other patient had had herpes simplex encephalitis with destruction that was confined to the left cerebral hemisphere. The lesion again mainly encompassed the left temporal lobe, but also extended to the left inferior frontal gyrus. Cognitive outcomes in the two patients were compared with each other and with published results from patients with semantic dementia. This is because, whereas the majority of semantic dementia patients present with more prominent atrophy of the left rostroventral temporal lobe, they invariably have a degree of atrophy in the mirror region on the right that progresses. Semantic dementia therefore provides no clear evidence about the specific role of the left rostroventral temporal lobe. The two patients showed a highly consistent cognitive profile. Their deficits were also similar in many respects to that observed in patients with mild-moderate semantic dementia, including severe anomia that was not resolved by phonological cues and impairment on non-verbal as well as verbal semantic tasks. Certain key features of the semantic dementia profile, however—including sensitivity to the familiarity and typicality of the stimulus materials—appeared only in tasks requiring verbal output in these two patients with unilateral left temporal lesions. Results in these cases provide some of the first definitive evidence regarding the specific functions of the left anterior temporal lobe. Highlights: Temporal lobe atrophy in semantic dementia (SD), even if asymmetrical, is bilateral. We studied two patients, one following stroke and one HSVE. Both had lesions encompassing nearly the whole left temporal lobe. Both cases had semantic memory deficits somewhat resembling SD. The specific features of SD only emerged in semantic tests requiring speech output.